Monitoring of Pediatric Type 1 Diabetes - Marks, Brynn E.; Wolfsdorf, Joseph I. (Frontiers in Endocrinology, 2020)
Regular self-monitoring of blood glucose levels, and ketones when indicated, is an essential component of type 1 diabetes (T1D) management. Although fingerstick blood glucose monitoring has been the standard of care for decades, ongoing rapid technological developments have resulted in increasingly widespread use of continuous glucose monitoring (CGM). This article reviews recommendations for self-monitoring of glucose and ketones in pediatric T1D with particular emphasis on CGM and factors that impact accuracy and real-world use of this technology.